Tentative Application of a Streamlined Protocol to Determine Organ-Specific Regulations of Deiodinase 1 and Dehalogenase Activities as Readouts of the Hypothalamus-Pituitary-Thyroid-Periphery-Axis - Renko, Kostja; Kerp, Helena; Pape, Janina; Rijntjes, Eddy; Burgdorf, Tanja; Führer, Dagmar; Köhrle, Josef (Frontiers in Toxicology, 2022)
In animal studies, both in basic science and in toxicological assessment of potential endocrine disruptors, the state of the thyroid hormone (TH) axis is often described and defined exclusively by the concentrations of circulating THs and TSH. Although it is known that the local, organ-specific effects of THs are also substantially regulated by local mechanisms such as TH transmembrane transport and metabolism of TH by deiodinases, such endpoint parameters of the axis are rarely assessed in these experiments. Currently developed in vitro assays utilize the Sandell-Kolthoff reaction, a photometric method of iodide determination, to test the effect of chemicals on iodotyrosine and iodothyronine deiodinases. Furthermore, this technology offers the possibility to determine the iodine content of various sample types (e.g., urine, ex vivo tissue) in a simple way. Here, we measured deiodinase type 1 and iodotyrosine dehalogenase activity by means of the Sandell-Kolthoff reaction in ex vivo samples of hypo- and hyperthyroid mice of two age groups (young; 3 months and old; 20 months). In thyroid, liver and kidney, organ-specific regulation patterns emerged across both age groups, which, based on this pilot study, may serve as a starting point for a deeper characterization of the TH system in relevant studies in the future and support the development of Integrated Approach for Testing and Assessment (IATA).